Enhanced electron emission from ternary solid solution-MWCNT hybrid with theoretical validation. (1st June 2021) - Ghosh, Shrabani; Maity, Supratim; Chandra, Ankita; Das, Bikram Kumar; Besra, Nripen; Sarkar, Samrat; Sarkar, Sourav; Chattopadhyay, K.K.
Abstract: Coalescence of unique properties of semiconductor and carbon nanotubes (CNTs) produces new advanced materials with exciting properties, which unwraps several new fields. Here, finite element modeling is employed to optimize the diameter of semiconducting zinc cadmium sulfide (Zn0.8 Cd0.2 S) microspheres on the wall of metallic CNTs to get the improved field emission property. Then, Zn0.8 Cd0.2 S microspheres are attached on COOH functionalized multiwalled CNTs (MWCNTs) by a simple one step solvothermal method for experimental corroboration. Field emission experiment shows a considerable enhancement of current density with respect to bare microspheres and functionalized CNTs. The turn-on field is found to be as low as 3V/μm at a current density of 10 μΑ/cm 2 for the hybrid system. Density functional theory (DFT) calculation is carried out for the model structures of Zn0.8 Cd0.2 S and CNT-Zn0.8 Cd0.2 S to calculate the work functions. This improvement in field emission property of the hybrid system is demonstrated in terms of band bending, geometry, high field enhancement factor, low work function and electron affinity. Thus, non-field emitting microspheres with less toxicity have been transformed into a decent field emitter by the contribution of few carbon nanotubes. Graphical abstract: Image 1 Highlights: ANSYS simulation specifies the optimized diameter of zinc cadmium sulfide (Zn0.8 Cd0.2 S) microsphere on carbon nanotube (CNT) to be 140-160 nm for enhanced field emission with respect to CNT and Zn0.8 Cd0.2 S, independently. Zn0.8 Cd0.2 S microspheres with optimized diameters are attached on the small amount of CNTs via a simple solvothermal method. Theoretically work function of the hybrid system (CNT-Zn0.8 Cd0.2 S) is calculated which is lower than Zn0.8 Cd0.2 S. Experimentally field emission is enhanced for hybrid system (CNT-Zn0.8 Cd0.2 S) which validates ANSYS simulation.